A New Zealander's Comments on American Legal Education - McGechan, R O (Victoria University of Wellington Law Review, 1999)
The author compares the teaching methods in law schools in the United States and New Zealand. The author first notes a comparison between direct lecturing and case method, finding merit in both. The author then points out that students' interest and enthusiasm often wane by second and third year, whether in New Zealand or America. The prestige of the American institutions' law reviews is also discussed, as well as some features of educational institutions (including classroom sizes and the curriculum). The author also discusses the New Zealand law school approach of getting part-time work experience while studying law. The author concludes that legal education needs a balance between the practical and the theoretical.